Transnational Sport : Gender, Media, and Global Korea - Joo, Rachael Miyung, 1975- (Book collections on Project MUSE., 2012)
Anthropologist Rachael Joo explores the gendered and mediated role of sports in producing a Korean sense of self on a global stage.